Using a Token Economy to Treat Escape-Maintained Problem Behavior Without Extinction. Issue 1 (January 2022) - Andzik, Natalie; Smith, Elle; Neef, Nancy
The use of extinction procedures when treating escape-maintained problem behavior can be undesirable and impractical for practitioners to use. To mitigate the risks associated with escape extinction, we explored the effectiveness of a delayed reinforcement token system without the use of extinction in school and home settings to treat escape-maintained problem behavior of students with autism spectrum disorder. In lieu of escape extinction (e.g., blocking), the researchers implemented a 30 s break contingent on problem behaviors and a token (to be exchanged at the end of the session) contingent on compliance. The results of a multiple probe design indicated substantial increases in compliance and reductions in problem behavior for all four participants. These findings suggest that extinction is not necessary to eliminate escape-maintained problem behavior in children with autism.